Global Economic Prospects and the Developing Countries 2002 : making trade work for the world's poor (the international bank for reconstruction and development, 2002)
Realizing the promise of the new global initiatives to expand trade requires concerted effort to move development to center stage in trade policy formulation. This report is dedicated to that agenda. It begins with a review of global prospects and ways globalization links the fates of industrial and developing countries. The report then considers issues in four broad areas that are particularly important to developing countries: merchandise trade, services, transport, and intellectual property rights. A final chapter summarizes the forward-looking policy agenda, and assesses the potential impact of further global integration and more rapid growth for the standards of living in poor countries everywhere.